Geopolymer Bio-Patch Repair: Microbially-Induced Calcite and Pozzolanic Fly Ash and Rice Husk Ash for Corrosion-Resistant of Reinforced Concrete Repair - Pinta Astuti; Angga Jordi Wisnu Nouvaldi; Aprilia Rahmayanti; Pramudya Surya Shabura; Muhammad Etandra Fara Adzani; Dylan Ataa Tsany; Adhitya Yoga Purnama; Rahmita Sari Rafdinal (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Indonesia’s archipelagic environment subjects concrete structures to severe corrosion and sulfate attacks, necessitating sustainable repair solutions. This study evaluates a geopolymer-based bio-patch repair mortar utilizing fly ash (FA), rice husk ash (RHA), and Bacillus subtilis bacteria to induce Microbially Induced Calcite Precipitation (MICP). While the silica-rich ashes act as pozzolanic materials, the bacteria enhance durability by reducing oxygen levels and lowering corrosion rates. Microscopic analysis confirmed the formation of calcium carbonate (CaCO_3) and calcium silicate hydrate (C-S-H), both of which significantly improve mechanical properties. The research identified an optimum mixture of 93% FA, 6% RHA, and 1% bacteria, which achieved a compressive strength of 30 MPa, a density of 2.32 g/cm³, and a low water absorption rate of 3.25%. These results meet standard performance requirements, demonstrating that this eco-friendly geopolymer-MICP system is a viable and innovative contribution to structural repair in aggressive environments.